Cooperation and the Rural Problem of India - Strickland, C. F. (Quarterly Journal of Economics, 1929)
Importance of agriculture, — Literacy and sanitation, 501. — Agricultural holdings, 506. — Backwardness of agriculture, 508. — Peasant indebtedness, 510. — Coöperative credit institutions, 514. — Agricultural Department activities, 518. — Further coöperation in agriculture, 520. — Popular education, 522. — Coöperative activities therein, 525. — Public health, 526. — Coöperative activities therein, 528. — Rural Community Councils, 530.